Self–tuning fuzzy PID decoupling controller for VAV air–conditioning system. (10th March 2014) - Vosoughi, Soheil; Balochian, Saeed; Gordan, Hodeiseh
One of the most important challenges in nonlinear, multi–input and multi–output (MIMO) and time variant systems is designing a controller with acceptable performance. This paper focuses on design a new adaptive fuzzy PID decoupling controller, applied in the VAV air–conditioning system. In this approach, the PID parameters are adjusted by fuzzy rules. Diagonal matrix decoupling method is employed to eliminate the coupling between the loop of supply air temperature and that of thermal–space air temperature. Therefore, combined adaptive method and PID controllers can solve the uncertainty challenge in the PID parameters. The simulation results confirm the effectiveness of the proposed control methodology.